The portrayal of characters through dialogue and action in isiXhosa drama : dramatic and cultural perspectives - Yantolo-Sotyelelwa, Betty Matase (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (African Languages))--University of Stellenbosch, 2005.